Cadmium ion detection membrane, preparation method thereof and application thereof in cadmium detection device

By using porous nanofiber membranes made of polylactic acid polymer materials and small molecule detection element loaded with cadmium ion, the existing cadmium ion detection technology is solved, and the problem of cumbersome operation and inconvenient for rapid on-site detection is achieved, achieving high sensitivity and rapid detection Effect, suitable for a variety of application scenarios.

CN115897058BActive Publication Date: 2025-02-14HANGZHOU JIASHENG BIO-DIGITAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211493875.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-02-14
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The existing cadmium ion detection technology mostly relies on large analytical instruments, which are cumbersome, time-consuming and inconvenient for rapid on-site detection. The small molecule fluorescent probes are not practical in actual detection.

Method used

Using a porous nanofiber membrane made of polylactic acid polymer material, the membrane is loaded with cadmium ion small molecule detection element (fluorescent probe), and effectively complexes cadmium ions using its internal pores and hydrophilic environment to achieve trace cadmium Fast and sensitive detection of ions.

Benefits of technology

This cadmium ion detection membrane significantly improves detection speed and sensitivity, and can achieve rapid and sensitive detection at a concentration level of 10-8mol/L. Its preparation method is simple and low-cost, and it is suitable for rapid detection kits for environmental protection and food safety. Test strips and sewage purification film products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115897058B_ABST
    Figure CN115897058B_ABST
Patent Text Reader

Abstract

The present application relates to the field of cadmium ion detection technology, and in particular to a cadmium ion detection membrane, a preparation method thereof, and its application in a cadmium detection device. The present application uses an environmentally friendly and processable polylactic acid polymer material as a carrier, based on the polymer / solvent / non-solvent ternary system phase separation mechanism, and adopts electrospinning technology to prepare the cadmium ion detection membrane. The film is porous inside and is formed by nanofibers. It has the advantages of high specific surface area, large porosity, and controllable fiber structure. It can significantly improve the detection speed and detection sensitivity and can be used for 10 ‑8 The invention provides a rapid and sensitive detection of cadmium ions at a concentration level of mol / L. The preparation method of the cadmium ion detection membrane is simple, and the comprehensive manufacturing cost of the target product is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cadmium ion detection, and in particular to a cadmium ion detection membrane, a preparation method thereof, and an application thereof in a cadmium detection device. Background Art

[0002] Cadmium ions have the characteristics of bioaccumulation, long half-life, and difficulty in decomposition. Once they enter the human body through the food chain and accumulate in the body, they can cause human lung dysfunction, renal insufficiency, calcium metabolism disorder, bone damage, and greatly increase the risk of cancer. Cadmium analysis and monitoring technology is the basis and prerequisite for the prevention and control of cadmium pollution. However, the current mature cadmium ion detection technology mostly relies on large-scale analytical instruments. Sample testing must be carried out by professional technicians in laboratories, and the operation is cumbersome, time-consuming, and expensive. Therefore, in environmental monitoring and environmental protection, rapid and on-site detection of trace cadmium ions is still a challenge, and it is urgent to further develop new methods and new materials for high-sensitivity and high-selectivity cadmium ion detection.

[0003] Among various detection methods, fluorescence technology has become the most commonly used method for cadmium ion detection due to its high sensitivity, strong specificity, simple operation, real-time monitoring, and fast response time. For example, the patent with publication number CN109897628A, "A fluorescent probe for detecting cadmium ions, its preparation method and application", the patent with publication number CN105548109B, "A fluorescent detection system and detection method for heavy metal cadmium", and the patent with publication number CN201310137848.4, "Fluorescent probe benzothiazole-terpyridine compounds for distinguishing and detecting zinc ions and cadmium ions, and preparation and application methods thereof", all report different types of cadmium ion fluorescent probes. Although these probes have high selectivity and sensitivity to cadmium ions, most of them are small molecule fluorescent probes, which are not very practical in actual detection. Summary of the invention

[0004] Using fluorescent probe, cadmium ions can be efficiently and sensitively detected, but because cadmium ion fluorescent probe often needs to be configured into liquid state to realize detection range, detection is inconvenient, and it is difficult to recycle probe after reaction is completed. In order to enhance the practicality of probe, the present application embodiment provides a kind of cadmium ion detection film, the film is loaded with cadmium ion small molecule detection primitive (fluorescent probe), and there is porous nano-micro fiber, and the pore and hydrophilic environment inside it can be effectively complexed to cadmium ions, so that the porous nano-micro fiber film is used for the application of trace cadmium ion detection. The cadmium ion detection film can be developed into environmental protection and food safety rapid detection kit, test strips and sewage purification membrane products, with broad market prospects.

[0005] In addition, the cadmium ion detection membrane uses environmentally friendly and processable polylactic acid polymer as a carrier, based on the polymer / solvent / non-solvent ternary system phase separation mechanism, and is made using electrospinning technology. The prepared cadmium ion detection membrane is porous inside and formed by nanofibers. It has the advantages of high specific surface area, large porosity, and controllable fiber structure. It can significantly improve the detection speed and sensitivity and can be used for 10 -8 Rapid and sensitive detection of cadmium ions at mol / L concentration level. In addition, the preparation method of the cadmium ion detection membrane is simple, and the comprehensive manufacturing cost of the target product is low. To this end, the embodiments of the present application disclose at least the following technical solutions:

[0006] In a first aspect, the present application discloses a method for preparing a cadmium ion detection membrane, comprising the following steps:

[0007] obtaining a first solution containing polylactic acid;

[0008] adding a cadmium ion fluorescent probe to the first solution to form a second solution; and

[0009] Using the second solution to perform high-voltage electrospinning to obtain the porous nanofiber membrane;

[0010] Wherein, the cadmium ion fluorescent probe is selected from

[0011]

[0012] In a second aspect, the present application discloses a cadmium ion detection membrane, comprising:

[0013] A nanofiber carrier formed of polylactic acid and a cadmium ion fluorescent probe embedded in the nanofiber carrier, wherein the cadmium ion fluorescent probe is selected from

[0014]

[0015] In a third aspect, the embodiments of the present application further disclose the use of the cadmium ion detection membrane prepared by the preparation method of the first aspect or the cadmium ion detection membrane described in the second aspect in a cadmium ion detection device.

[0016] The technical effects of the cadmium ion detection membrane, its preparation method and application provided in the embodiments of the present application will be specifically described in the embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Scanning electron microscope images of the cadmium ion detection membrane provided in Example 1 of the present application (a) 50000×, (b) 200000×.

[0018] Figure 2These are optical photographs of the cadmium ion detection membrane provided in Example 2 of the present application before and after being acted upon by cadmium ions of different concentrations.

[0019] Figure 3 This is a fluorescence spectrum diagram of the cadmium ion detection membrane provided in Example 3 of the present application before and after being acted on by cadmium ions of different concentrations.

[0020] Figure 4 The fluorescence spectra of the cadmium ion detection membrane provided in Examples 1 to 4 of the present application (Figures A to D) are incubated with EDTA in a solution system containing cadmium ions.

[0021] Figure 5 The fluorescence spectra of the solution system containing cadmium ions incubated with the cadmium ion detection membrane and EDTA are provided for comparative examples 1 to 2 of the present application (Figures A to B). DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. The reagents not described separately in detail in the present application are all conventional reagents and can be obtained from commercial channels; the methods not described in detail are all conventional experimental methods and can be obtained from the prior art.

[0023] Fluorescent probes can be used to detect cadmium ions efficiently and sensitively. However, since cadmium ion fluorescent probes often need to be prepared in a liquid state to achieve the detection range, detection is inconvenient. In order to realize the circulation and recycling of cadmium ion fluorescent probes, the present application discloses a cadmium ion detection membrane and a preparation method thereof.

[0024] In some embodiments, the cadmium ion detection membrane comprises a nanofiber carrier formed of polylactic acid and a cadmium ion fluorescent probe embedded in the nanofiber carrier, wherein the cadmium ion fluorescent probe is selected from

[0025]

[0026] like Figure 1 As shown in the figure, the cadmium ion fiber membrane can be formed into porous nanofibers, there is no beading phenomenon between the fiber filaments, the fiber filament diameter distribution is concentrated, and no particles appear. Figure 2 As shown, the average diameter of the nanofibers in the cadmium ion detection membrane provided in the embodiment of the present application is 135.2±24.2nm, and the water absorption rate is 23.7-34.7%. Figure 3 As shown, the detection limit of cadmium ions of the cadmium ion detection membrane provided in the embodiment of the present application is 10 -8mol / L, and visual detection can be achieved. As shown in the table, the longitudinal breaking strength of the cadmium ion detection membrane provided in the embodiment of the present application is 46.4-62.7MPa, and the breaking elongation is 540.5-726.6%, which shows that it has excellent mechanical properties. Figure 4 As shown, the cadmium ion detection membrane provided in the embodiment of the present application has excellent porosity, and the fluorescent probe has a polymethylpyridine ring that gives it stronger hydrophilicity, so that the liquid to be detected can penetrate into the cadmium ion detection membrane, thereby improving the detection capacity and detection efficiency.

[0027] To this end, in some embodiments, the preparation method of the fluorescent probe of the cadmium ion detection membrane includes:

[0028] obtaining a first solution containing polylactic acid;

[0029] adding a cadmium ion fluorescent probe to the first solution to form a second solution; and

[0030] Using the second solution to perform high-voltage electrospinning to obtain the porous nanofiber membrane;

[0031] Wherein, the cadmium ion fluorescent probe is selected from

[0032]

[0033] In some embodiments, the solvent in the first solution and the solvent in the second solution are both selected from at least one of dichloromethane, isopropanol, n-butanol, propanol, tetrahydrofuran, ethyl acetate or chloroform. In some optional embodiments, the solvent in the first solution and the solvent in the second solution are both a mixed solvent of dichloromethane and tetrahydrofuran, and the volume ratio of dichloromethane to tetrahydrofuran in the mixed solvent is 3 to 6:1.

[0034] In some embodiments, the high-voltage electrospinning conditions are: power supply voltage 13 kV to 20 kV, the distance between the needle and the receiving substrate is 14 cm to 18 cm, and the feed rate is 0.5 mL / h to 1.5 mL / h.

[0035] In some embodiments, the structural formula of polylactic acid (PLA) is as follows:

[0036] Wherein, n is a natural number; optionally, the molecular weight of the polylactic acid is not less than 50,000.

[0037] In some embodiments, the content of the cadmium ion fluorescent probe in the second solution is 2-3.5 mg / mL, and the content of the polylactic acid in the second solution is 100-300 mg / mL.

[0038] Example 1

[0039] Polylactic acid (poly (L-lactic acid), molecular weight 85000-160000, CAS No.: 26161-42-2, MDL No.: MFCD00166383, purchased from Sigma-Aldrich) was accurately weighed and dissolved in a mixed solvent, wherein the mixed solvent was a mixed solution of dichloromethane and tetrahydrofuran in a volume ratio of 4:1, to prepare a first solution with a PLA concentration of 0.15 g / mL.

[0040] The cadmium ion fluorescent probe is accurately weighed and added to the first solution to obtain a second solution, and the PD1 content in the second solution is 2.5 mg / mL and the PLA concentration is 0.15 g / mL. The molecular structure of the cadmium ion fluorescent probe is: For the synthesis of cadmium ion fluorescent probe, please refer to "Synthesis and Application Research of Polypyridyl-Linked Porphyrin_Liu Shufang [D] Hunan University Master's Thesis Page 21".

[0041] The second solution was loaded into a 10 mL syringe as the electrospinning solution and connected to a high-voltage electrospinning machine (TL-L-Pro-10W, Shenzhen Tongli Micro-Nano Technology Co., Ltd.). Electrospinning was performed under the conditions of a power supply voltage of 15 kV, a distance of 15 cm between the needle and the receiving substrate, and a feed rate of 0.5 mL / h. After spinning, the obtained cadmium ion detection membrane was vacuum dried to obtain a finished product.

[0042] Example 2

[0043] In Example 2, polylactic acid (PLA) was dissolved in a mixed solvent of dichloromethane (DCM) and tetrahydrofuran (THF) (the volume ratio of dichloromethane to tetrahydrofuran was 5:1) to prepare a solution with a PLA concentration of 0.2 g / mL; the cadmium ion small molecule detection element PD2 was added to the PLA solution obtained above to obtain a PD2 / PLA solution with a PD2 content of 2 mg / mL and a PLA concentration of 0.2 g / mL. This PD2 / PLA solution was added to a disposable syringe and connected to an electrospinning device. Under the spinning conditions of a power supply voltage of 16 kV, a distance of 15 cm between the needle and the receiving substrate, and a feeding speed of 0.8 mL / h, a cadmium ion detection membrane loaded with PD2 was obtained. Among them,

[0044] use (According to the method provided by "Kruper WJ; Chamberlin TA, Kochanny M.Regiospecific arylr nitration of meso-substituted tetraarylporphyrins: a simple route to bifunctional porphyrins. Journal of Organic Chemistry, 1989, 54(11): 2753-2756", the compound in Example 1 is first nitrated with nitric acid under a nitrogen atmosphere, and then reacted with SnCl2·2H2O in concentrated hydrochloric acid to obtain a cadmium ion fluorescent probe.

[0045] Example 3

[0046] In Example 3, polylactic acid (PLA) was dissolved in a mixed solvent of dichloromethane (DCM) and tetrahydrofuran (THF) (the volume ratio of dichloromethane to tetrahydrofuran was 6:1) to prepare a solution with a PLA concentration of 0.25 g / mL; the cadmium ion small molecule detection element PD3 was added to the PLA solution obtained above to prepare a PD2 / PLA solution with a PD3 content of 2.5 mg / mL and a PLA concentration of 0.25 g / mL. This PD3 / PLA solution was added to a disposable syringe and connected to an electrospinning device. Under the spinning conditions of a power supply voltage of 18 kV, a distance of 16 cm between the needle and the receiving substrate, and a feed rate of 1.2 mL / h, a cadmium ion detection membrane loaded with PD3 was obtained. Among them, the PD3 / PLA solution was added to a disposable syringe and connected to an electrospinning device. Under the spinning conditions of a power supply voltage of 18 kV, a distance of 16 cm between the needle and the receiving substrate, and a feed rate of 1.2 mL / h, a cadmium ion detection membrane loaded with PD3 was obtained. (According to the method provided in "Kruper WJ; Chamberlin TA, Kochanny M. Regiospecific arylr nitration of meso-substitutedtetraarylporphyrins: a simple route to bifunctional porphyrins. Journal of Organic Chemistry, 1989, 54(11): 2753-2756", the compound in Example 1 is nitrated with nitric acid under a nitrogen atmosphere to obtain a cadmium ion fluorescent probe.

[0047] Example 4

[0048] In Example 4, the properties of polylactic acid used are: molecular weight 60000, CAS number: 26100-51-6, MDL number: MFCD00081867, purchased from Sigma-Aldrich. Other raw materials and spinning conditions are the same as those in Example 1 to prepare a cadmium ion detection membrane.

[0049] Comparative Example 1

[0050] In Comparative Example 1, (Synthesized with reference to the method provided in "Design, preparation and detection performance study of cadmium ion fluorescent probe based on biological applications_Huang Wenbin [D] Zhejiang University master's thesis page 17") as a cadmium ion fluorescent probe, other raw materials and spinning conditions are the same as in Example 1 to prepare a cadmium ion detection membrane.

[0051] Comparative Example 2

[0052] In Comparative Example 2, the polylactic acid used is: poly (D, L-lactic acid), linear molecular formula: (C6H8O4) n , CAS No.: 26680-10-4, molecular weight of 18000-24000, purchased from Sigma-Aldrich. Other raw materials and spinning conditions were the same as those in Example 1 to prepare a cadmium ion detection membrane.

[0053] Application Example 1

[0054] Example 2 Colorimetric response of the cadmium ion detection membrane prepared in Example 2 to different concentrations of cadmium ions: Cadmium nitrate was dissolved in distilled water to prepare aqueous solutions of different concentrations. The cadmium ion detection membrane loaded with PD1 was soaked in ethanol for 20 minutes and then soaked in cadmium ion solutions of different concentrations for 10 minutes, and then dried to observe the color change of the fiber membrane. Figure 2 As shown in the figure, the originally reddish brown fiber membrane turned into grass green after reacting with cadmium ions, and the green color deepened further with the increase of cadmium ion concentration. This shows the ability of the cadmium ion detection membrane to visually detect cadmium ions.

[0055] Application Example 2

[0056] The cadmium ion detection membrane prepared in Example 3 responds to the fluorescent signals of cadmium ions of different concentrations: Since the cadmium ion fluorescent probe can coordinate with cadmium ions and cause changes in the probe fluorescence signal, the cadmium ion detection membrane loaded with the fluorescent probe can be used for the fluorescence detection of cadmium ions. The specific process is as follows: Dissolve cadmium nitrate in distilled water to prepare aqueous solutions of different concentrations. Soak the cadmium ion detection membrane loaded with PD1 in ethanol for 20 minutes, and then soak it in the above-mentioned cadmium ion solutions of different concentrations for 10 minutes, and then dry it, and test the fluorescence spectrum changes in a fluorescence spectrometer. The results are as follows. Figure 3 As shown. Figure 3 It can be seen that with the increase of cadmium ion concentration, the fluorescence intensity of the cadmium ion detection membrane at 648nm gradually decreases, and the fluorescence intensity at 612nm gradually increases, showing a ratiometric fluorescence response. Due to the large specific surface area and porosity of the cadmium ion detection membrane, the sensitivity of the detection is significantly improved, and a detection rate of 10 -8 Rapid and sensitive detection of cadmium ions at mol / L concentration level.

[0057] Application Example 3

[0058] Control group: Cadmium nitrate was dissolved in distilled water to prepare aqueous solutions with different concentrations of 0.1 μM. The films provided in Examples 1 to 4 and Comparative Examples 1 to 2 were soaked in ethanol for 20 minutes and then in cadmium ion solutions for 10 minutes, and then dried. The fluorescence spectrum changes were tested in a fluorescence spectrometer.

[0059] Test group: Cadmium nitrate was dissolved in distilled water to prepare aqueous solutions with different concentrations of 0.1 μM. After the films provided in Examples 1 to 4 and Comparative Examples 1 to 2 were immersed in ethanol for 20 minutes, the films and an aqueous solution of 0.1 μM EDTA (equal volume to the cadmium ion solution) were simultaneously added to six parallel cadmium ion aqueous solutions and immersed for 10 minutes, and then dried, and the fluorescence spectrum changes were tested in a fluorescence spectrometer.

[0060] The results are as follows Figure 4 and 5 As shown, the fluorescence of the control group is lower at 612nm and higher at 648nm. After adding EDTA, the fluorescence intensity of the test group at 612nm is significantly reduced, while the fluorescence intensity at 648nm is increased. In addition, the cadmium ion detection membrane provided by Examples 1 to 4 has a significantly greater reduction in 612nm than Comparative Example 2 ( Figure 5 B), while the cadmium ion detection membrane provided in Comparative Example 1 had almost no significant difference between the control group and the test group.

[0061] This shows that in the presence of a competitive chelating agent, the cadmium ion detection membranes provided in Examples 1 to 4 release the binding with cadmium ions, while the comparative example 1 has almost no release effect, and the film provided in comparative example 2 has an insignificant release effect. This shows that the cadmium ion detection membrane provided in the embodiments of the present application is reversible in the complexation of cadmium ions, and can be recycled, which is beneficial to saving resources and costs.

[0062] Performance Analysis Example 1

[0063] According to GB / T 13 022-91 "Test Method for Tensile Properties of Plastic Films", a universal material testing machine (HSK-S, UK) was used to measure the tensile strength σ and elongation at break ε of the film. The film sample was cut into 5 cm rectangular strips, and the two ends of the sample to be tested were fixed on the clamp of the strength machine. The machine was started, and the stretching was stopped immediately after the film broke.

[0064] The tensile strength was calculated as σ = F / b·d, where F is the breaking load, b is the width of the specimen, and d is the thickness of the specimen.

[0065] The elongation at break is calculated as ε=ΔL / L×100%, wherein ΔL is the increment of the clamp spacing when breaking, and L is the initial clamp spacing.

[0066] According to the above method, the mechanical properties of the cadmium ion detection membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are tested, and the results are shown in Table 1. As can be seen from Table 1, the tensile strength of the insulator detection membrane provided in the embodiment of the present application is 47.4 to 62.7 MPa, and the elongation at break is 540.5 to 726.6%. However, since Comparative Example 2 uses polylactic acid with a lower molecular weight, its mechanical properties are not as good as those of the embodiment. Comparative Example 1 uses a completely different cadmium ion fluorescent probe, but its mechanical properties are still not as good as those of Examples 1 to 4. This may be because the fluorescent probe used and the polylactic acid cannot form microscopic pores during the process of forming a film, which reduces the mechanical properties of its nanofibers.

[0067] Table 1

[0068] Implementation σ(MPa) ε(%) Example 1 52.5±4.9 604.8±53.6 Example 2 57.5±5.2 678.3±48.3 Example 3 54.5±6.7 627.4±39.7 Example 4 50.8±3.4 593.4±52.9 Comparative Example 1 38.5±4.2 235.7±37.2 Comparative Example 2 25.7±2.3 218.4±39.5

[0069] Performance Analysis Example 2

[0070] In this experiment, the hydrophilicity and hydrophobicity of the membrane surface were characterized by measuring the water contact angles of the membrane surfaces prepared in Examples 1 to 4 and Comparative Examples 1 to 2. The measurement was performed using a contact angle meter (SL200C, China). The dried flat membrane was cut into strips of 5 cm × 1 cm in the longitudinal and transverse directions, and the contact angles of 5 different positions of each sample membrane were measured, and the results were averaged.

[0071] This performance analysis example also measured the water absorption rate of the membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2. Each cadmium ion detection membrane sample was cut into 5 cm × 5 cm and immersed in deionized water for 24 hours. After reaching swelling equilibrium, it was taken out, and the water on the surface of the membrane was quickly absorbed with filter paper and weighed to obtain Ww. After drying at 45°C to constant weight, it was weighed to obtain Wd, and calculated according to water absorption rate = (Ww-Wd) / Wd×100%.

[0072] Table 2

[0073] Implementation Contact angle (°) Water absorption (%) Example 1 4.8±0.4 27.2±2.1 Example 2 4.4±0.2 31.5±3.2 Example 3 4.3±0.1 28.4±1.4 Example 4 4.9±0.3 25.9±2.2 Comparative Example 1 58.4±2.7 6.4±0.8 Comparative Example 2 5.0±0.5 21.1±1.7 PLA Film 150.3±4.2 3.9±0.5

[0074] Table 2 lists the contact angle and water absorption results of the cadmium ion detection membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2, respectively. A PLA membrane was prepared by electrospinning the solution prepared with polylactic acid used in Example 1 in the same manner as in Example 1, and its contact angle and water absorption were analyzed.

[0075] As shown in Table 2, the contact angles of the cadmium ion detection membranes provided in Examples 1 to 4 are significantly lower than those of the PLA membrane and lower than those of Comparative Example 1, which indicates that the PLA membrane is almost non-hydrophilic, and the fluorescent probe used in Comparative Example 1 has a decisive influence on improving the hydrophilicity of the cadmium ion detection membrane. The water absorption rate of the cadmium ion detection membranes provided in Examples 1 to 4 is significantly higher than that of the PLA membrane and Comparative Example 1. This shows that the cadmium ion detection membrane prepared by electrospinning the above-mentioned fluorescent probe and polylactic acid in the embodiments of the present application has excellent hydrophilicity and water absorption rate, so that it can adsorb more cadmium ions in aqueous solution, has a higher detection capacity, and gives it higher detection efficiency and detection sensitivity when used as a cadmium ion detection membrane.

[0076] The cadmium ion detection membrane prepared based on the above embodiment has excellent cadmium ion detection sensitivity, water permeability and mechanical properties, so that it has a recyclable detection characteristic for cadmium ions and can be used to prepare cadmium ion detection devices. In some embodiments, the cadmium ion detection device includes an environmental protection and food safety rapid detection kit, a test strip, and a sewage purification membrane product, which shows that the application prospect of the cadmium ion detection membrane is broad.

[0077] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be covered within the protection scope of the present application.

Claims

1. A method for preparing a cadmium ion detection membrane, characterized in that: The steps include: A first solution containing polylactic acid is obtained; the structural formula of the polylactic acid is Wherein, n is a natural number, and the molecular weight of the polylactic acid is not less than 50000; adding a cadmium ion fluorescent probe to the first solution to form a second solution, wherein the content of the cadmium ion fluorescent probe in the second solution is 2 to 3.5 mg / mL, and the content of the polylactic acid in the second solution is 100 to 300 mg / mL; and Using the second solution to perform high-voltage electrospinning to obtain the cadmium ion detection membrane; Wherein, the cadmium ion fluorescent probe is selected from 2. The preparation method according to claim 1, characterized in that: The solvent in the first solution and the solvent in the second solution are both selected from at least one of dichloromethane, isopropanol, n-butanol, propanol, tetrahydrofuran, ethyl acetate or chloroform.

3. The preparation method according to claim 2, characterized in that: The solvent in the first solution and the solvent in the second solution are both a mixed solvent of dichloromethane and tetrahydrofuran, and the volume ratio of dichloromethane to tetrahydrofuran in the mixed solvent is 3 to 6:

1.

4. The preparation method according to claim 1, characterized in that: The high-voltage electrospinning conditions are: power supply voltage 13 kV to 20 kV, the distance between the needle and the receiving substrate is 14 cm to 18 cm, and the feeding speed is 0.5 mL / h to 1.5 mL / h.

5. A cadmium ion detection membrane, characterized in that, It comprises a nanofiber carrier formed of polylactic acid and a cadmium ion fluorescent probe embedded in the nanofiber carrier, wherein the cadmium ion fluorescent probe is selected from The structural formula of the polylactic acid (PLA) is Wherein, n is a natural number, and the molecular weight of the polylactic acid is not less than 50,000.

6. The cadmium ion detection membrane according to claim 5, characterized in that The average diameter of the nanofibers is 135.2±24.2 nm, and the water absorption rate is 23.7-34.7%.

7. The cadmium ion detection membrane according to claim 5, characterized in that The detection limit of the cadmium ion detection membrane for cadmium ions is 10 -8 mol / L.

8. The cadmium ion detection membrane according to claim 5, characterized in that The longitudinal breaking strength of the cadmium ion detection membrane is 46.4-62.7 MPa, and the breaking elongation is 540.5-726.6%.

9. Use of the cadmium ion detection membrane prepared by the preparation method described in any one of claims 1 to 4 or the cadmium ion detection membrane described in any one of claims 5 to 8 in a cadmium ion detection device.

Citation Information

Patent Citations

  • Benzothiazole-terpyridine fluorescent probes for distinguishing between zinc and cadmium ions, their preparation and application methods.

    CN103265539B

  • A fluorescence detection system and method for the heavy metal cadmium

    CN105548109B

  • Fluorescent probe for detecting cadmium ions and preparation method and application thereof

    CN109897628A